The remains of war : bodies, politics, and the search for American soldiers unaccounted for in Southeast Asia - Hawley, Thomas M., 1970- (Politics, history, and culture., 2005)
An exploration of how US' efforts to sacralize and repatriate the remains of some 2,000 soldiers killed in action in the Vietnam War might indicate some lingering corporeal and ontological uncertainties in the post-Vietnam era.